2018
DOI: 10.1111/jnu.12451
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction With Work–Family Balance Mediates the Relationship Between Workplace Social Support and Depression Among Hospice Nurses

Abstract: Purpose The purpose of this study was to investigate the relationship between social support (from personal and workplace sources) and psychological distress (depression, anxiety, and stress symptoms), as well as to examine the mediating role of satisfaction with work–family balance among hospice nurses. Design and Method A cross‐sectional study design was utilized with a sample of 90 hospice nurses from the southern United States. Participants completed online surveys, including (a) the Depression, Anxiety, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 36 publications
4
39
0
4
Order By: Relevance
“…The two dimensions of job burnout (except DP) and perceived social support were negatively correlated, partially confirming H4. Barnett et al (2019) found workplace social support, not personal social support, was associated with lower psychological distress; Sadaaki Fukui found (Fukui et al, 2019) that supervisory support had positive effects in reducing turnover intention through reduced EE. The study indicated that in the workplace the support from supervisors and colleagues was more important than that of family and friends (Fukui et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The two dimensions of job burnout (except DP) and perceived social support were negatively correlated, partially confirming H4. Barnett et al (2019) found workplace social support, not personal social support, was associated with lower psychological distress; Sadaaki Fukui found (Fukui et al, 2019) that supervisory support had positive effects in reducing turnover intention through reduced EE. The study indicated that in the workplace the support from supervisors and colleagues was more important than that of family and friends (Fukui et al, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that women physicians tend to display more empathy and report especially high empathic concern for patients (Gleichgerrcht and Decety, 2013;Cho and Jeon, 2019). Moreover, women are more likely than male physicians to counsel their patients and spend more time with each patient (Barnett et al, 2019). They also shoulder the responsibility of taking care of their own families, raising children, caring for the elderly and so on.…”
Section: Discussionmentioning
confidence: 99%
“…The well-being of workers is essential for the health of society [49]. Balancing work and family life in the nursing sector to achieve a high degree of well-being is crucial for the development of the service [53], since well-being impacts the quality of patient care [54], with poor well-being increasing the risk of negligence and/or abuse [55].…”
Section: Managing Demands Control and Support In An Organizational Cmentioning
confidence: 99%
“…However, and fortunately for workers, WLB is becoming a trendy topic in recent years [19] in the personal sphere and also in the organizational context [20]. Although the sectors studied are diverse, recent studies on the topic focus on health [21][22][23][24], transport [25], or education [26,27]. The study of WLB is specifically prominent in the field of public health [3].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, more focused on the impact on work, indicates that WLB is an organizational lever reducing stress and willingness to exit for employees of the organization [29]. Moving to a rich WLB, literature indicates that WLB helps in the development of psychological availability and augmenting employee positive energy [30], and highlights that the satisfaction level with the WLB plays a role in supporting mental health [22]. Others works have indicated that WLB has a positive effect on job and family satisfaction [31], and recently it has been proved that a positive correlation exists between job satisfaction and WLB [24].…”
Section: Introductionmentioning
confidence: 99%